Pendampingan Penentuan Harga Pokok Produksi Dan Harga Pokok Penjualan Bagi Umkm Kota Bogor - Jan Horas Veryady Purba; Sudradjat Sudradjat; Maju Lumban Tobing; Tri Marlina (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This Community Service Activity aims to provide assistance to Bogor City MSMEs so that they are able to calculate the Cost of Goods Production as a basis for determining Product Selling Prices. MSMEs in Indonesia are the main driver of the economy. Apart from that, there are several obstacles faced by MSME players. One of these obstacles is the lack of knowledge of MSME actors in financial aspects, such as determining the Cost of Goods Production (HPP) as a basis for determining the selling price of products. This problem is also felt by Bogor City MSME business actors. Therefore, this community service activity was carried out to help solve this problem. The aim of this activity is to increase the understanding of MSME actors in determining the Cost of Production (HPP) and selling prices. The method of this activity is carried out by providing counseling and at the same time direct assistance to Bogor City MSMEs. The results of this community service are marked by the participants' enthusiasm and ability to receive the material and being able to carry out practice in calculating production costs, cost of production and cost of goods sold as well as the cost of each product as a basis for determining the selling price. The results of this activity are very beneficial for City MSMEs Bogor. Keywords: Cost of Production, Selling Price. MSMEs